The Association Between Religious Belief and Postoperative Psychological Status and Quality of Life of Parents of Children with Congenital Heart Disease: dA Single Center Experience in Southeast China - Lin, Wen-Hao (Journal of religion and health, 2024)
This study aimed to investigate the association of religious belief on the postoperative psychological status and quality of life of parents of children with congenital heart disease (CHD). This was a cross-sectional study conducted at a provincial children's hospital in Fujian Province, China. Parents of postoperative children with CHD in the early postoperative period were included in this study between January 2020 and September 2020. The parents were divided into a religious belief group (n = 39) and a nonreligious belief group (n = 42) depending on whether they had religious beliefs. The Religious Coping Questionnaire, WHOQOL-BREF scale, Self-rating depression scale (SDS), and Self-rating anxiety scale (SAS) were used to evaluate psychological status and quality of life. The results showed that the SDS and SAS scores in the religious belief group were significantly lower than those in the nonreligious belief group (P = 0.012 and P = 0.003, respectively). The WHOQOL-BREF scale results showed that the religious belief group's score was significantly higher than those in the nonreligious belief group on the subscale scores of physiology, psychology, social relations, and environment on the WHOQOL-BREF. The total score of quality of life in the religious belief group was significantly higher than that in the nonreligious belief group. Religious belief was associated with lower SDS score (β = − 0.324, P = 0.005) and SAS score (β = − 0.245, P = 0.026), while religious belief was positively correlated with the score of WHOQOL-BREF (β = 0.506, P < 0.001). In this study, we concluded that comparing to those with no religious beliefs, parents with religious belief experienced more positive emotions and higher quality of life when taking care of children in the early postoperative period after congenital heart surgery.